2019
DOI: 10.1371/journal.pone.0204387
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of miR-10b in B-RafV600E dependent anchorage independent growth and invasion of melanoma cells

Abstract: Recent high-throughput-sequencing of cancer genomes has identified oncogenic mutations in the B-Raf genetic locus as one of the critical events in melanomagenesis. B-Raf encodes a serine/threonine kinase that regulates the MAPK/ERK kinase (MEK) and extracellular signal-regulated kinase (ERK) protein kinase cascade. In normal cells, the activity of B-Raf is tightly regulated and is required for cell growth and survival. B-Raf gain-of-function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…MiR-483-5p (Figure 5B) and miR-10b (Figure 5C) exhibited the greatest decrease and increase in transcription, respectively, in FLC relative to NML (Figure 5A). It has been reported in other cancer types (35)(36)(37) that miR-10b is transcriptionally activated by the Twist1 transcription factor, and we identified a ~3-fold increase of TWIST1 expression in FLC (Supplemental Figure 3A). However, we observed that increasing patient age at the time of surgery.…”
Section: Resultssupporting
confidence: 67%
“…MiR-483-5p (Figure 5B) and miR-10b (Figure 5C) exhibited the greatest decrease and increase in transcription, respectively, in FLC relative to NML (Figure 5A). It has been reported in other cancer types (35)(36)(37) that miR-10b is transcriptionally activated by the Twist1 transcription factor, and we identified a ~3-fold increase of TWIST1 expression in FLC (Supplemental Figure 3A). However, we observed that increasing patient age at the time of surgery.…”
Section: Resultssupporting
confidence: 67%
“…MiR-483-5p (Figure 5B) and miR-10b (Figure 5C) exhibited the greatest decrease and increase in transcription, respectively, in FLC relative to NML (Figure 5A). It has been reported in other cancer types (35)(36)(37) that miR-10b is transcriptionally activated by the Twist1 transcription factor, and we identified a ~3-fold increase of TWIST1 expression in FLC (Supplemental Figure 3A). However, we observed that increasing patient age at the time of surgery.…”
Section: Resultssupporting
confidence: 67%
“…MiR-483-5p (Figure 5B) and miR-10b (Figure 5C) exhibited the greatest decrease and increase in transcription, respectively, in FLC relative to NML (Figure 5A). It has been reported in other cancer types (35)(36)(37) that miR-10b is transcriptionally activated by the Twist1 transcription factor, and we identified a ~3-fold increase of TWIST1 expression in FLC (Supplemental Figure 3A). However, we observed that increasing patient age at the time of surgery.…”
Section: Resultssupporting
confidence: 67%